2015
DOI: 10.2340/00015555-2123
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Multiple Lentigines in LEOPARD Syndrome with PTPN11 Gene Mutation

Abstract: LEOPARD syndrome (LS) is an autosomal dominant condition with multiple anomalies, including multiple lentigines. LS is caused by mutations in PTPN11, encoding the protein tyrosine phosphatase, SHP-2. We report here 2 unrelated Japanese cases of LS with different PTPN11 mutations (p.Y279C and p.T468P). To elucidate the pathogenesis of multiple lentigines in LS, ultrastructural and immunohistochemical analyses of lentigines and non-lesional skin were performed. Numerous mature giant melanosomes in melanocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This makes SHP-2 a bidirectional regulator for cytokines and growth-factors-mediated signal transduction. A previous study has shown [14] that abnormal expression of SHP-2 can promote the initiation, progression, and metastasis of breast cancer, gastric cancer, liver cancer, lung cancer, and other cancers. Therefore, there is great significance in prevention and treatment of glioma through studying the role and mechanism of SHP-2 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This makes SHP-2 a bidirectional regulator for cytokines and growth-factors-mediated signal transduction. A previous study has shown [14] that abnormal expression of SHP-2 can promote the initiation, progression, and metastasis of breast cancer, gastric cancer, liver cancer, lung cancer, and other cancers. Therefore, there is great significance in prevention and treatment of glioma through studying the role and mechanism of SHP-2 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the gain-of-function changes resulting in excessive PTPN11 activity in NS (12), LS mutants are catalytically defective and exert a dominant negative effect (22), suggesting that mutation type and region are important in the underlying pathogenic mechanisms and differential diagnoses of NS and LS. A recent study has suggested that LS-associated mutations may increase melanin synthesis in melanocytes via the activation of Akt/mammalian target of rapamycin signaling, thus, resulting in a phenotype with multiple lentigines (23). …”
Section: The Rasopathies With Calmmentioning
confidence: 99%
“…PTPN11 mutations have been extensively investigated in the past years. Germline mutations in PTPN11 cause Noonan syndrome (9)(10)(11) and its clinically related Leopard syndrome (12), whereas somatic mutations of PTPN11 contribute to leukemogenesis (13)(14)(15)(16)(17), as well as in the development of specific solid tumors, including neuroblastoma (18,19), metachondromatosis (20,21), brain tumors (22)(23)(24), neurofibromatosis (25), optic nerve pilomyxoid astrocytoma (26), breast carcinoma (27,28), colorectal cancer (29,30) and Ewing sarcoma (31). However, oncogenic mutations of PTPN11 are rare in the majority of solid tumors including GC (32,33).…”
Section: Introductionmentioning
confidence: 99%